Accuracy of Low Haemoglobin Level in Predicting No-Reflow Phenomenon in Primary Percutaneous Coronary Intervention Patients - Nazir, Maria; Chaudry, Azhar Ali; Iqbal, Usman; Bhatti, Qamar-Uz-Zaman; Ali, Gulzar; Paiker, Sarwat (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the accuracy of low haemoglobin level in predicting the no-reflow phenomenon in patients undergoing primary percutaneous coronary intervention. Study Design: Analytical cross-sectional study Study Setting and Duration: Armed Forces Institute of Cardiology and National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, (from Dec 2024 to May 2025) Methods: A total of 115 patients aged 30-70 years, regardless of gender, with acute STEMI undergoing PPCI were enrolled through consecutive sampling. Post-coronary artery bypass graft (CABG) patients, those who had received glycoprotein IIb/IIIa inhibitors before the procedure, patients presenting beyond 24 hours of symptom onset, with chronic kidney disease, and with a history of major bleeding or haemorrhagic disorders were excluded. Low haemoglobin was defined as <11.5 g/dL. The no-reflow phenomenon was described as TIMI flow grade <3. Results: Among 115 patients [105(91.3%) male; median age 57.00(51.00–62.00) years], no-reflow was observed in 30(26.1%) patients. Patients with low haemoglobin (<11.5 g/dL) experienced higher no-reflow than with normal haemoglobin (p=0.018). The sensitivity and specificity were 16.7% and 97.6%, respectively, with a positive predictive value (PPV) of 71.4%, a negative predictive value (NPV) of 76.8%, and an overall diagnostic accuracy of 76.5%. Conclusion: Low haemoglobin level demonstrated high specificity but poor sensitivity in predicting the no-reflow phenomenon following PPCI.